Predicting COVID-19 Peaks Around the World - Tsallis, Constantino; Tirnakli, Ugur (Frontiers in Physics, 2020)
The official data for the time evolution of active cases of COVID-19 pandemics around the world are available online. For all countries, a peak has been either observed (China and South Korea) or is expected in the near future. The approximate dates and heights of those peaks have important epidemiological implications. Inspired by similar complex behavior of volumes of transactions of stocks at the NYSE and NASDAQ, we propose a q-statistical functional form that appears to describe satisfactorily the available data for all countries. Consistently, predictions of the dates and heights of those peaks in severely affected countries become possible unless efficient treatments or vaccines, or sensible modifications of the adopted epidemiological strategies, emerge.